Isolation and Characterization of Diesel-Degrading Bacteria from Hydrocarbon-Contaminated Sites, Flower Farms, and Soda Lakes - Gessesse Kebede Bekele; Solomon Abera Gebrie; Eshetu Mekonen; Tekle Tafese Fida; Adugna Abdi Woldesemayat; Ebrahim M. Abda; Mesfin Tafesse; Fasil Assefa (International Journal of Microbiology)
Hydrocarbon-derived pollutants are becoming one of the most concerning ecological issues. Thus, there is a need to investigate and develop innovative, low-cost, eco-friendly, and fast techniques to reduce and/or eliminate pollutants using biological agents. The study was conducted to isolate, characterize, and identify potential diesel-degrading bacteria. Samples were collected from flower farms, lakeshores, old aged garages, asphalt, and bitumen soils and spread on selective medium (Bushnell Haas mineral salt agar) containing diesel as the growth substrate. The isolates were characterized based on their growth patterns using optical density measurement, biochemical tests, and gravimetric analysis and identified using the Biolog database and 16S rRNA gene sequencing techniques. Subsequently, six diesel degraders were identified and belong to Pseudomonas, Providencia, Roseomonas, Stenotrophomonas, Achromobacter, and Bacillus. Among these, based on gravimetric analysis, the three potent isolates AAUW23, AAUG11, and AAUG36 achieved 84%, 83.4%, and 83% diesel degradation efficiency, respectively, in 15 days. Consequently, the partial 16S rRNA gene sequences revealed that the two most potent bacterial strains (AAUW23 and AAUG11) were Pseudomonas aeruginosa, while AAUG36 was Bacillus subtilis. This study demonstrated that bacterial species isolated from hydrocarbon-contaminated and/or uncontaminated environments could be optimized to be used as potential bioremediation agents for diesel removal.